정서학대와 신체학대의 법적 정의와 관계에 대한 연구 - 우리나라 정서학대에 대한 최초 대법원판결을 중심으로 - 이세원(Lee Sewon) (사회복지법제연구, 2019)
판결은 국민에게 있어 법의 잣대가 된다. 따라서 본 연구는 사법부에서 정서학대와 신체학대를 어떻게 정의하고 있으며, 어떠한 관계로 판단하고 있는지에 대하여 분석하였다. 이를 위해 우리나라 정서학대에 대한 최초의 대법원 판결(대법원 2011도6015)을 중심으로 유사한 범죄사실에 대한 사건 3개의 하급심과 상고심 판결문을 사례분석하였다. 분석 결과, 판례에서는 ‘아동의 정신 및 신체의 건강과 발달에 해를 끼치는 행위’로 신체학대와 정서학대를 정의하기 보다는 유형력과 신체손상을 기준으로 구분하고 있다. 그렇기 때문에 본 연구의 대상이 되었던 육아지원기관에서의 아동학대 사례와 같은 경우, 정서학대와 신체학대의 중복학대를 인정하지 않았다. 나아가, 재판부는 정서학대를 ‘신체학대로까지 미치지 않은 학대’로 봄으로써 신체학대보다 심각성에 대해 깊이 고려하고 있지 않은 것으로 분석되었다. 이와 같은 연구 결과에 따라 사법의 판단이 일반국민과 육아지원기관 전문직의 ‘아동학대인지 감수성’을 높일 수 있도록 하기 위하여, 신체학대와 정서학대에 대한 상상적 경합의 적용, 아동학대범죄의 특수성을 고려한 실제적 사법 판단 등의 제언을 하였다. This study analyzes how the judiciary defines emotional abuse and physical abuse and cognizes relations between the two types of abuse. The first Supreme Court of South Korea ruling on emotional abuse (2011 Supreme Court Decision Do6015) and three similar criminal cases have been analyzed by case study method. The findings of the study are as follows. First, judicial precedent has distinguished emotional abuse and physical abuse as ‘exertion and body injury’ rather than ‘acts that harm the child’s emotional and physical health or normal growth’. Second, the judiciary has not recognized emotional abuse and physical abuse together in cases such as the subject of this study. Third, the court has regarded emotional abuse as ‘abuse that has not yet been reached to physical abuse’. This study suggests that the courts should apply an apply an compound crimes of criminal law article 40 in respect to emotional abuse and physical abuse and develop practical judgements in consideration of the specialty and differentiation of child abuse cases. These suggestions will contribute to enhancing ‘child abuse sensibility’. KCI Citation Count: 9